A Meta-Analysis of the Analgesic Efficacy of Single-Doses of Ibuprofen Compared to Traditional Non-Opioid Analgesics Following Third Molar Surgery - Lorenzo Franco-de la Torre; Norma Patricia Figueroa-Fernández; Diana Laura Franco-González; Ángel Josabad Alonso-Castro; Federico Rivera-Luna; Mario Alberto Isiordia-Espinoza (MDPI AG, 2021)
The purpose of this systematic review was to determine the analgesic efficacy and adverse effects of ibuprofen in comparison with other traditional non-opioid analgesics after third molar surgery. A total of 17 full texts were identified in PubMed and assessed using the Cochrane Collaboration's risk of bias tool by two independent researchers. The sum of pain intensity differences, total pain relief, the overall evaluation, the number of patients requiring rescue analgesics, and adverse effects were collected. Data were analyzed using the Review Manager Software 5.3. for Windows. A total of 15 articles met the criteria. The qualitative and quantitative analysis showed that ibuprofen is more effective to relieve post-operative dental pain than acetaminophen, meclofenamate, aceclofenac, bromfenac, and aspirin. Moreover, ibuprofen and traditional non-steroidal anti-inflammatory drugs have a similar safety profile. In conclusion, ibuprofen 400 mg appears to have good analgesic efficacy and a safety profile similar to other traditional non-steroidal anti-inflammatory drugs after third molar surgery.